La Despenalización del Aborto a Consecuencia de la Figura de Incesto - Cabrera Dávila, Jason Fernando (2016)
The following investigational project titled “THE DEPENALIZATION OF THE ABORTION AS A CONCEQUENCE OF THE FIGURE OF INCEST” In which it makes reference to the socio-judicial problem in the actuality where Ecuador lives because of the high rate of incestuous pregnancies. This investigational work exposes the risks of acquiring psychological and health problems, which women face because of not having an abortion when it is a product of incest. Add to that the legislative basis that women have an abortive intervention if needed or already in the process of abortion pregnant women adds. The Ecuadorian criminal standard allows the abortion in women when their health is affected or there is danger of death; and, when the rape was to a woman with mental health problems, why limit the ability of them to opt for an abortion to be punishable by law if this is done under another figure. Nevertheless, nobody takes in to consideration those pregnancies that were the product of incest, which are shown to put in risk the mother because she could acquire physical or mental problems that greatly affects the psych of the woman. In addition, the risk of manifestation of possible malformations, 5 mental incapacities, physical and psychological illnesses to the child born of incest; due to inbreeding increases, the genetic percentage is affected. In the present investigation, additional to the recompilation of information, surveys and interviews were done to lawyers, legal doctors and ex-judges in the Loja Province. Corroborating that women who decide to terminate the pregnancy due to the product of incest are with a legal framework that criminalizes the conduct and puts at risk their mental health and physical integrity by exposing them to an unsafe abortion that is done in a clandestine manner without the appropriate instruments or specialized professionals, why also are necessary for a legal reform is implemented for the rule to focus on also protect the victim wellbeing of women, and giving rise to that you can decide on their reproduction even more so when it comes to an incestuous pregnancy which is not desired or planned.